Nilai-Nilai Pendidikan Islam dalam Ada' Tuho Ulumanda dan Implementasinya di Pondok Pesantren Darul Ulum Desa Popenga Kecamatan Ulumanda Kabupaten Majene (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to examine and analyze the Islamic educational values ​​contained in the local tradition of Ada' Tuho Ulumanda and its implementation at the Darul Ulum Islamic Boarding School, Popenga Village, Ulumanda District, Majene Regency. The Ada' Tuho tradition is one of the cultural heritages of the Ulumanda community that is full of moral, social, and spiritual values ​​that are closely related to the principles of Islamic education, especially the values ​​of faith, morals, and society. In the context of Muslim society, local traditions are not only seen as cultural symbols, but also function as a medium for transmitting religious values ​​that strengthen Islamic identity while maintaining social harmony. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The data obtained are analyzed thematically to reveal the Islamic educational values ​​contained in the practice of Ada' Tuho and its form of implementation in the Islamic boarding school environment. The results of the study indicate that the Ada' Tuho tradition contains a number of important values, including: the value of monotheism that emphasizes faith and respect for God's power, moral values ​​that include honesty, responsibility, discipline, and respect for parents and others, and social values ​​in the form of solidarity, mutual cooperation, deliberation, and justice in community life. The implementation of these values ​​at the Darul Ulum Islamic Boarding School is carried out through a formal learning process, habituation of worship, exemplary behavior of the ustaz, and strengthening the character of students based on the integration of Islamic values ​​and local wisdom. Thus, the Islamic boarding school plays a role as an agent of preserving religious culture that is able to harmonize Islamic teachings with local traditions constructively, making it relevant to strengthening contextual Islamic education in the modern era.